Download presentation

Published byDouglas Wilkerson Modified over 8 years ago

1
**Solving Quadratic Equations by Completing the Square**

Day 1: Section 9 – 3

2
Main Ideas Solve quadratic equations by finding the square root. Solve quadratic equations by completing the square.

3
**Determine if the quadratic is a perfect square.**

x2 + 4x + 4 = x2 + 2(2)x + 22 = (x+2)2

4
Complete the Square 1.) m2 + 12m + 36 = m2 + 2(6)m + 62 = (m + 6)2 2.) r2 – 6r + 9 = r2 + 2(-3)r + (-3)2 = (r – 3)2 3.) x2 – 2x + 1 = x2 + 2(-1)x + (-1)2 = (x – 1)2

5
Solve x2 – 2x + 1 = 9 x2 – 2x + 1 = 9 x2 + 2(-1)x + (-1)2 = 9 (x – 1)2 = 9 x = or x = x = 4 or x = -2 Solution Set: {-2, 4}

6
Solve x2 – 4x + 4 = 5 x2 – 4x + 4 = 5 x2 + 2(-2)x + (-2)2 = 5 (x – 2)2 = 5 Solution Set: {-0.2, 4.2}

7
**x = {-5, 1} x = -2 + 3 x = 1 x = -2 – 3 x = -5 1.) x2 + 4x + 4 = 9**

x2 + 4x + 4 = 9 x2 + 2(x)(2) + (2)2 = 9 (x + 2)2 = 9 x + 2 = ±3 x = -2 ± 3 x = -2 ± 3 x = -2 – 3 x = -5 x = {-5, 1}

8
3.) x2 – 8x + 16 = 5 3.) x2 – 8x + 16 = 5 x2 – 2(x)(4) + (4)2 = 5 (x – 4)2 = 5 x ≈ {1.8, 6.2}

9
**Solving Quadratic Equations by Completing the Square**

Section 9 – 3 Day 2

10
Steps 1.) Find 2.) Find 3.) Add to ax2 + bx

11
**Find the value of c that makes it a perfect square.**

x2 + 6x + c Step 1: Step 2: (3)2 = 9 Step 3.) c = 9 Check: x2 + 6x + 9 = (x + 3)2

12
**Find the value of c that makes it a perfect square.**

x2 – 8x + c Step 1: Step 2: (-4)2 = 16 Step 3.) c = 16 Check: x2 – 8x + 16 = (x - 4)2

13
**Solve x2 + 6x + 3 = 10 by completing the square**

x2 + 6x = 7 Since add 9 to each side x2 + 6x + 9 = 7 + 9 x2 + 2(x)(3) + (3)2 = 16 (x + 3)2 = 16 x + 3 = ±4 x = -3 ± 4 x = -3 ± 4 x = x =1 x = x = -7 x = {-7, 1}

14
t2 – 4t + 3 = 0 t = 2 + 1 t = 3 t2 – 4t + 3 = 0 t2 – 4t = t2 – 4t = -3 t2 + 2(t)(-2) + (-2)2 = -3 + (-2)2 t2 – 4t + 4 = (t – 2)2 = 1 t – 2 = ±1 t = 2 ±1 t = 2 ±1 t = 2 - 1 t = 1 t = {1,3}

15
**t = {-9,-1} y2 + 10y = -9 t = -5 + 4 t = -1 t = -5 - 4 t = -9**

y2 + 10y = -9 y2 + 2(y)(5) + (5)2 = -9 + (5)2 y2 + 10y + 25 = y2 + 10y + 25 = 16 (t + 5)2 = 16 t + 5 = ±4 t = -5 ±4 t = -5 ±4 t = t = -1 t = t = -9 t = {-9,-1}

Similar presentations

© 2024 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google